MENGIDENTIFIKASI KESULITAN BELAJAR SISWA KELAS IV DI UPT SD NEGERI 064966 MEDAN PERJUANGAN TAHUN AJARAN 2023/2024 - Nur Intan Humairoh (Trapsila: Jurnal Pendidikan Dasar, 2023)
This study aims to explore the difficulty of learning mathematics in grade 4 students at UPT SD Negri 064966 Medan Perjuangan and the factors that cause these learning difficulties. The type in this study is a type of qualitative research with a qualitative descriptive approach, and the data collection method used is the interview method.  The interview was conducted with a grade IV teacher of UPT SD Negri 064966 Medan Perjuangan. The subjects of this study were students in class IV of UPT SD Negri 064966 Medan Perjuangan. The results showed that factors that affect student learning difficulties include low student attitudes and interests towards mathematics subjects, diverse student abilities, classroom learning is still dominated by the use of books as the main source and limited facilities and infrastructure